If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (-20) = -41 x + -20 = -41 Reorder the terms: -20 + x = -41 Solving -20 + x = -41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + x = -41 + 20 Combine like terms: -20 + 20 = 0 0 + x = -41 + 20 x = -41 + 20 Combine like terms: -41 + 20 = -21 x = -21 Simplifying x = -21
| 16x^2-87-144=0 | | x+32=7x-4 | | 2x-.2=.2x | | 2y=4x+-2 | | 4x+5.5y=25 | | 2X+36=-X^2 | | 21=4x+37 | | 5-4(x-1)=y | | 5x-13x+x=7x+8 | | 11-3(8+3p)=49 | | 7x-3-2x=-48 | | 2-r=-7 | | 11+m=.25-2m | | 3e+2(e+5)=-3f | | y^2-14y=4x-53 | | 66=2x+3(4x-6) | | 170*0.10=153 | | 2[3x+7]=2[4x-2] | | 26-3y=18 | | 152=19n | | 6w-3h=bforh | | 18t-23=-15 | | x^3-4x^2-7x=0 | | ln(x)(x^9+6)= | | 170*0.10= | | p-(-3)=-7 | | 33.8=(1.8*C)+32 | | -4(5x+3)=19x+4 | | 5=2x-3x-1 | | 21-4x=20 | | 14-7g+3=8g-83-19g | | 9r-3+8r=15 |